Effect of vitamin K intake on the stability of oral anticoagulant treatment: dose-response relationships in healthy subjects - Schurgers, Leon J.; Shearer, Martin J.; Hamulyák, Karly; Stöcklin, Elisabeth; Vermeer, Cees (Blood, 2004)
Oral anticoagulants exert their effect by blocking the utilization of vitamin K, yet little is known about competitive aspects of their interaction with dietary vitamin K. We carried out systematic dose-response studies in healthy volunteers who had been stably anticoagulated and maintained on their individualized doses for 13 weeks. First, we studied the response to weekly incremental doses (50 μg-500 μg) of vitamin K1 supplements (K1) taken daily for 7 days. The threshold K1 dose causing a statistically significant lowering of the INR was 150 μg/day. In 25% of the participants the INR change was regarded as clinically relevant at a vitamin K intake of 150 μg/day. Circulating undercarboxylated osteocalcin did not decrease until 300 μg K1/day compared with 100 μg K1/day for undercarboxylated FII, suggesting differential antidotal effects on bone and hepatic γ-carboxylation. Next, we tested the response to vitamin K-rich food items. The short-lived response after meals of spinach and broccoli suggested an inefficient bioavailability from these 2 sources. We conclude that short-term variability in intake of K1 is less important to fluctuations in the international normalized ratio (INR) than has been commonly assumed and that food supplements providing 100 μg/day of vitamin K1 do not significantly interfere with oral anticoagulant therapy. (Blood. 2004;104:2682-2689)